Political Perceptions and Dynamics in The Formation of Southern Garut Regency: An Analysis of DPRD Members’ Perspectives - Suhendar, Usep; Djuyandi, Yusa; Solihah, Ratnia (GoAcademica Research & Publishing, 2024)
This research analyzes the political perceptions of faction members in the Garut Regency Regional House of Representatives (DPRD) regarding the formation of Southern Garut Regency. Findings indicate broad support for the expansion, motivated by the need to enhance public services, accelerate development, and improve community welfare in the southern region. Despite this, some factions express skepticism, emphasizing the necessity for in-depth studies and administrative readiness. Utilizing political perception theory, the study explores how DPRD members form their views based on information and interpret their political and social contexts. The research also highlights theoretical limitations, such as insufficient consideration of broader power dynamics and structural influences, including central government policies and local economic interests. These findings underscore the need for further theoretical development to comprehensively capture the complexities of the regional expansion process.